Mesenchymal stromal cells but not cardiac fibroblasts exert beneficial systemic immunomodulatory effects in experimental myocarditis. - Konstantinos Savvatis (Public Library of Science (PLoS), 2012)
Systemic application of mesenchymal stromal cells (MSCs) in inflammatory cardiomyopathy exerts cardiobeneficial effects. The mode of action is unclear since a sufficient and long-acting cardiac homing of MSCs is unlikely. We therefore investigated the regulation of the immune response in coxsackievirus B3 (CVB3)-induced acute myocarditis after intravenous application of MSCs. Wildtype mice were infected with CVB3 and treated with either PBS, human MSCs or human cardiac fibroblasts intravenously 1 day after infection. Seven days after infection, MSCs could be detected in the spleen, heart, pancreas, liver, lung and kidney, whereby the highest presence was observed in the lung. MSCs increased significantly the myocardial expression of HGF and decreased the expression of the proinflammatory cytokines TNFα, IL1β and IL6 as well as the severity of myocarditis and ameliorated the left ventricular dysfunction measured by conductance catheter. MSCs upregulated the production of IFNγ in CD4+ and CD8+ cells, the number of IL10-producing regulatory T cells and the apoptosis rate of T cells in the spleen. An increased number of CD4+CD25+FoxP3 could be found in the spleen as well as in the circulation. In contrast, application of human cardiac fibroblasts had no effect on the severity of myocarditis and the systemic immune response observed after MSCs-administration. In conclusion, modulation of the immune response in extracardiac organs is associated with cardiobeneficial effects in experimental inflammatory cardiomyopathy after systemic application of MSCs.